2019
DOI: 10.1080/15384101.2019.1624110
|View full text |Cite
|
Sign up to set email alerts
|

Role of autophagy in the regulation of adipose tissue biology

Abstract: Autophagy plays a key role in cellular homeostasis since it allows optimal cellular functioning and provides energy under conditions of stress. Initial is revealed that alterations of macroautophagy disturb adipogenic differentiation in cultured cells, and in mice, leading to a drastic reduction of adipose tissue depots. Nevertheless, more recent studies indicate that autophagy participates in the control of adipose tissue biology in a more complex manner. The protein TP53INP2 activates the formation of autoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…The severity of autophagy may be indicated by increased levels of phosphatidylethanolamines since it was previously found that the level of degradation products of these phospholipids (lysophosphatidylethanolamines) is reduced in psoriasis granulocytes [ 12 ]. In contrast, by coupling with LC3, phosphatidylethanolamines participate in the formation of the autophagosomes necessary to start the protein degradation process [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The severity of autophagy may be indicated by increased levels of phosphatidylethanolamines since it was previously found that the level of degradation products of these phospholipids (lysophosphatidylethanolamines) is reduced in psoriasis granulocytes [ 12 ]. In contrast, by coupling with LC3, phosphatidylethanolamines participate in the formation of the autophagosomes necessary to start the protein degradation process [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a process in which cytoplasmic macromolecules and organelles are degraded by lysosomes [ 27 ] and plays a crucial role in adipose tissue homoeostasis [ 28 ]. The biological functions of autophagy in adipose tissue have been studied in humans and model animals, but autophagy studies have rarely been reported in chicken abdominal fat.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is required for lipid storage during white adipocyte differentiation [47]. Hyperactivation of autophagy was observed in adipocyte hypertrophy, and obese and diabetic patients [48]. WAT to beige or BAT transdifferentiation has been recognized as a potential therapeutic target for obesity and related metabolic disease prevention and management [49].…”
Section: Discussionmentioning
confidence: 99%